2007
DOI: 10.1038/sj.onc.1210545
|View full text |Cite
|
Sign up to set email alerts
|

TRPV6 channel controls prostate cancer cell proliferation via Ca2+/NFAT-dependent pathways

Abstract: The transient receptor potential channel, subfamily V, member 6 (TRPV6), is strongly expressed in advanced prostate cancer and significantly correlates with the Gleason >7 grading, being undetectable in healthy and benign prostate tissues. However, the role of TRPV6 as a highly Ca 2 þ -selective channel in prostate carcinogenesis remains poorly understood. Here, we report that TRPV6 is directly involved in the control of prostate cancer cell (LNCaP cell line) proliferation by decreasing: (i) proliferation rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
207
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(222 citation statements)
references
References 25 publications
13
207
0
2
Order By: Relevance
“…As can be observed from our experiments, inhibition of CaV3.2 channels by either siRNAs or inhibitors does not totally abolish PAP secretion. This may reflect the participation of other calcium channels in secretion such as TRPV6 channels, which have been shown to be expressed in prostate LNCaP cells and to participate to basal calcium entry (35). In addition, we confirm that T-type calcium channels can be activated by phorbol esters (PMA) as previously shown by others (28).…”
Section: Discussionsupporting
confidence: 71%
“…As can be observed from our experiments, inhibition of CaV3.2 channels by either siRNAs or inhibitors does not totally abolish PAP secretion. This may reflect the participation of other calcium channels in secretion such as TRPV6 channels, which have been shown to be expressed in prostate LNCaP cells and to participate to basal calcium entry (35). In addition, we confirm that T-type calcium channels can be activated by phorbol esters (PMA) as previously shown by others (28).…”
Section: Discussionsupporting
confidence: 71%
“…It has been documented for half a century that low [Ca 2 þ ] induces colon cell proliferation in vitro and in vivo. 46,47 Although several recent studies have shown that TRPV6 overexpression is often associated with increased cell proliferation in colon, breast, and prostate cancers, [48][49][50] it is not clear how an increase in TRPV5/6 levels leads to elevated proliferation. The Ca 2 þ deficiency-induced and Trpv5/6-dependent IGF signaling unraveled by this study provides a possible mechanistic explanation for the elevated epithelial cell proliferation in Ca 2 þ deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this notion, it was shown that the proliferation-promoting action of a1-adrenoreceptor (a1-AR) agonists on prostate cancer (PCa) cells is based on preferred coupling of the a1-AR-coupled signalling pathway to activation of a member of transient receptor potential (TRP) channel family, TRPC6, Ca 2þ influx through which in turn specifically regulates NFAT in a Ca 2þ /calcineurin-dependent manner [17]. In addition, in LNCaP PCa cells yet another highly oncogenic TRP member, TRPV6 [18], was shown to support high proliferation rates apparently by providing constitutive Ca 2þ influx required for subsequent downstream NFAT activation [19]. TRPV6 expression in PCa cells is also positively regulated by vitamin D3 receptor (VDR) activation to enhance [Ca 2þ ] C and proliferation of cells [20].…”
Section: Ca 2þ Remodelling That Promotes Proliferationmentioning
confidence: 99%
“…B 369: 20130097 are number of instances when apoptosis resistance is conferred by higher expression of Ca 2þ entry channels (figure 2). Indeed, it was shown that TRPV6 and ORAI3 not only promote proliferation, but also increase survival of PCa and breast cancer cells, respectively [19,20,24]. ORAI3-conferred survival of breast cancer cells involved Ca 2þ -dependent increase of c-Myc expression and activity resulting in the inhibition of pro-apoptotic Bax protein expression [24,25].…”
Section: Ca 2þ Remodelling In Conferring Apoptosis Resistancementioning
confidence: 99%
See 1 more Smart Citation